The education irony: when college degrees lead to unemployment, mindless thinking, debt, and despair - Hershey H. Friedman (Academia Mental Health & Well-Being)
Education’s role extends beyond job preparation; it should equally nurture students’ moral character, compassion, and civic duty. This essay argues that many higher education institutions fall short of their educational responsibilities. Instead of producing well-rounded individuals with strong ethical principles, critical thinking abilities, and job-ready skills, some schools may inadvertently stifle creativity and discourage open debate. The author suggests that a limited focus on particular ideological views and an overemphasis on identity politics can restrict students’ exposure to diverse perspectives. Rather than becoming adept at logical reasoning, students have become proficient in harmful binary thinking and pathological dualism—a mindset that is likely to lead to misery.